Putting the 'studies' back into metal music studies. (1st September 2018) - Savigny, Heather; Schaap, Julian
The field of metal music studies is in the ascendancy and has established itself as a legitimate domain of enquiry. In this article, we argue that the study of metal has the capacity not only to provide us with rich histories of the subculture and the experiences of fans as academics, but is able to (and should) contribute to wider concerns within society. We aim to answer three key questions that, we argue, underpin and legitimate academic enquiry of metal music: (1) why does the study of metal matter? (the need to ask and answer the 'so what?' question); (2) how does metal matter? (the case for methodological rigour) and finally, (3) epistemologically: how can we justify our claims to knowledge? As such, this article is a call to reflect on the wider questions and issues that underpin the study of metal and move the field beyond descriptive representational accounts.